2018
DOI: 10.37358/mp.18.3.5030
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of CAD/CAM Versus Traditional Interim Fixed Dental Prostheses

Abstract: The aim of this in vitro study is to compare the load-to-fracture performance of polymethyl methacrylates (PMMA) provisional restorations manufactured with a traditional laboratory technique in comparison to a computer-assisted design and computer-assisted manufacturing (CAD-CAM) technique. Five interim three-unit fixed dental prostheses were fabricated with the conventional indirect technique, on a standard typodont. The same model was scanned with an intraoral scanner and the digital design of identical fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Recently, a study conducted by Pop et al, in which fracture resistance of provisional restorations of 3-unit FPDs indirectly fabricated by two types of PMMA has been compared with those made of PMMA blocks by CAD/CAM technology. 23 They have demonstrated that fracture resistance in CAD/CAM technology was significantly higher than indirect method. In the study by Alt et al, it has been shown that fracture resistance of interim restorations of 3-unit FPDs fabricated directly by PMMA is lower than those fabricated by CAD/CAM PMMA blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study conducted by Pop et al, in which fracture resistance of provisional restorations of 3-unit FPDs indirectly fabricated by two types of PMMA has been compared with those made of PMMA blocks by CAD/CAM technology. 23 They have demonstrated that fracture resistance in CAD/CAM technology was significantly higher than indirect method. In the study by Alt et al, it has been shown that fracture resistance of interim restorations of 3-unit FPDs fabricated directly by PMMA is lower than those fabricated by CAD/CAM PMMA blocks.…”
Section: Discussionmentioning
confidence: 99%
“…However, addition of TEGDMA affects in general mechanical properties, raised water absorption and determine color instability. UDMA reduces the polymerization shrinkage and ensures flexural strength, elastic modulus and hardness of the material [27,28]. UDMA and TEGDMA https://doi.org/10.37358/MP.21.2.5473 have resembling modulus of elasticity, significantly higher than other monomers [25,29].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…This study aimed to evaluate fracture load of thin occlusal crowns fabricated of CAD/CAM PICN material under a static compressive load [27]. To evaluate the fracture resistance Engra & all recommends static load tests or flexural tests as best choice [20].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%